2015
DOI: 10.1186/s40658-015-0127-y
|View full text |Cite
|
Sign up to set email alerts
|

Method dependence, observer variability and kidney volumes in radiation dosimetry of 177Lu-DOTATATE therapy in patients with neuroendocrine tumours

Abstract: BackgroundRadionuclide therapy can be individualized by performing dosimetry. To determine absorbed organ doses in 177Lu-DOTATATE therapy, three methods based on activity concentrations are currently in use: the small volume of interest (sVOI) method, and two methods based on large VOIs either on anatomical CT (aVOI) or on thresholds on functional images (tVOI). The main aim of the present work was to validate the sVOI in comparison to the other two methods regarding agreement and time efficiency. Secondary ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 23 publications
0
32
1
2
Order By: Relevance
“…When a maximum tolerated BED of 38 Gy to the kidney or an absorbed dose of 2 Gy to the bone marrow was applied, the kidney was the dose-limiting organ in 87%. The maximum number of 7.4 GBq therapy cycles per patient was five (2-14) based on the absorbed dose limits 23 Gy to kidneys and 2 Gy to bone marrow and eight (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) cycles when based on the 38 Gy BED limit to the kidneys and 2 Gy absorbed dose to the bone marrow (Figure 3). According to these results, by using these absorbed dose limits, about 2/3 of patients could receive more than the four cycles that has been considered a gold standard, while some patients (12%) would reach the dose limit after only 2-3 cycles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When a maximum tolerated BED of 38 Gy to the kidney or an absorbed dose of 2 Gy to the bone marrow was applied, the kidney was the dose-limiting organ in 87%. The maximum number of 7.4 GBq therapy cycles per patient was five (2-14) based on the absorbed dose limits 23 Gy to kidneys and 2 Gy to bone marrow and eight (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) cycles when based on the 38 Gy BED limit to the kidneys and 2 Gy absorbed dose to the bone marrow (Figure 3). According to these results, by using these absorbed dose limits, about 2/3 of patients could receive more than the four cycles that has been considered a gold standard, while some patients (12%) would reach the dose limit after only 2-3 cycles.…”
Section: Resultsmentioning
confidence: 99%
“…The main aim of the Uppsala group, working on 177 Lu-DOTATATE PRRT dosimetry, has been dedicated to developing a clinically applicable and robust dosimetry protocol for solid organs based on 3-D imaging [19][20][21]. 177 Lu-DOTATATE PRRT dosimetry based on 2-D imaging suffers from problems when delineating healthy organ uptake due to overlaying uptake from tumors and physiological uptake in the bowel [8,27,28] and is instead best used to provide input data for cross-dose calculations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present work, the mean activity concentration was sampled with multiple small VOIs in a healthy homogeneous part of each source volume on SPECT images. This method was proposed and supported by Sandström et al [35]. First, they showed that, compared to activity quantification on SPECT images, quantification based on planar images might artificially increase TIAC by 100% for the left kidney close to the spleen and by 50% for the right kidney close to the liver.…”
Section: Discussionmentioning
confidence: 96%